1980
DOI: 10.1007/bf01953844
|View full text |Cite
|
Sign up to set email alerts
|

Insect antifeedant properties of withanolides and related steroids from Solanaceae

Abstract: Physalisperuviana shrubs were not attacked by larvae of Spodoptera littoralis. It was demonstrated that withanolide E, a steroid isolated from P.peruviana, as well as several related steroids, have insect antifeedant properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…In the second group, IV (withaferin A) and V (withanolide D) were inactive against S. littoralis at the screening dose of 0.01% used in the previous study (1). In the present work, these two compounds were not active according to our criterion of activity below the highest concentration tested, 0.1%.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In the second group, IV (withaferin A) and V (withanolide D) were inactive against S. littoralis at the screening dose of 0.01% used in the previous study (1). In the present work, these two compounds were not active according to our criterion of activity below the highest concentration tested, 0.1%.…”
Section: Discussionmentioning
confidence: 51%
“…In a recent study (1) it was shown that certain ergostane-type steroids isolated from the leaves of several solanaceous plants, as well as some closely related products (5), have a considerable antifeedant effect for larvae of a lepidopterous insect, the Egyptian cotton leafworm, Spodoptera littoralis (Boisd.). The most active compounds were withanolide E (I) and its 2,3-dihydro-l~-hydroxy derivative (III).…”
Section: Introductionmentioning
confidence: 99%
“…Withanolides exhibited a broad spectrum of biological properties and significant pharmacological activities, including insect-antifeedant, insect-repellent activities, hepatoprotective, immunomodulatory, antibacterial, anti-inflammatory, antitumor, cytotoxic activity, and protection against CCl 4 -induced hepatoxicity (Glotter, 1991;Lan et al, 2009;Veleiro, Oberti, & Burton, 2005). An insect-antifeedant property of withanolide E isolated from P. peruviana has been demonstrated against Spodoptera littoralis larvae (Ascher et al, 1980). Withanolide E and 4β-hydroxywithanolide E have been tested as anticancer agents (Cassady & Suffness, 1980).…”
Section: Withanolidesmentioning
confidence: 98%
“…The insect repellent and insecticidal properties of nicandrenone (189) and the insect antifeedant property of withanolide E (150) and of a number of related natural and synthetically modified withanolides have been studied (13,84,94,254). Further investigation of this property of withasteroids is expected to yield fruitful results.…”
Section: Biological Activity Of Withasteroidsmentioning
confidence: 98%
“…The key steps in the recent synthesis of this substance by PEREZ-MEDRANO and GRIECO (226) were the insertion of a hydroxyl group at the 14a-position and introduction of the 17J3-hydroxyl group. The former was achieved by a hetero Diels-Alder reaction between steroidal dienol acetate (252) and benzyl nitrosoformate and subsequent transformation of the desired adduct to 14a-hydroxy-17-oxo-androstane derivative (254). Attempts to introduce 17J3-hydroxyl group by addition of appro- References pp.…”
Section: Synthesis Of Withanolidesmentioning
confidence: 99%